Analisis Soal Hots Pada Buku Teks Kimia Kelas XI Semester Ganjil SMA/MA Di Palangka Raya - Sihombing, Juliana; Sidauruk, Suandi; Meiliawati, Ruli (Jurnal Ilmiah Kanderang Tingang, 2024)
This study aims to describe the HOTS aspects developed in chemistry textbooks for class XI odd semester SMA/MA in Palangka Raya based on the HOTS aspects according to Brookhart's theory. HOTS aspects in this study include: analyzing, evaluating, creating, reasoning and logic, decision making, problem solving, and creative thinking. The method used in this research is descriptive quantitative. The source of the data in this study was the question papers for Class XI Chemistry Textbooks for Odd Semester SMA/MA in Palangka Raya. The results of this study indicate that the percentage of HOTS aspects developed in Chemistry Textbook questions for Class XI Odd Semester SMA/MA in Palangka Raya is 43,9% consisting of 11,6% analyzing aspects, 8,4% reasoning and logic aspects, 3,9% aspects of decision making, and 20,0% aspects of problem solving, while aspects of evaluating, aspects of creating, and aspects of creative thinking are not developed in the textbooks analyzed. Thus, it can be concluded that the questions developed in the analyzed chemistry text books still pay little attention to HOTS aspects.